Functional Redundancy in bird community decreases with riparian forest width reduction. Issue 21 (11th October 2018) - Maure, Lucas A.; Rodrigues, Rodolpho C.; Alcântara, Ângelo V.; Adorno, Bruno F. C. B.; Santos, Douglas L.; Abreu, Eduardo L.; Tanaka, Rafael M.; Gonçalves, Rute M.; Hasui, Erica
Abstract: Riparian ecosystems are suffering anthropogenic threats that reduce biodiversity and undermine ecosystem services. However, there is a great deal of uncertainty about the way species composition of assemblages is related to ecosystem function, especially in a landscape fragmentation context. Here, we assess the impact of habitat loss and disturbance on Functional Diversity (FD) components Functional Redundancy (FRed), Functional Evenness (FEve), and Functional Richness (FRic) of riparian forest bird assemblages to evaluate (a) how FD components respond to riparian forest width reduction and vegetation disturbance; (b) the existence of thresholds within these relationships; (c) which of the main birds diet guild (frugivores, insectivores, and omnivores) respond to such thresholds. We predict that FD components will be affected negatively and nonlinearly by riparian changes. However, guilds could have different responses due to differences of species sensitivity to fragmentation and disturbance. We expect to find thresholds in FD responses, because fragmentation and disturbance drive loss of specific FD components. Our results show that FRed and FEve were linearly affected by width and disturbance of riparian habitats, respectively. FRed was significantly lower in riparian forests assemblages below 400 m wide, and FEve was significantly higher above 60% disturbance. These responses of FD were also followed to the decline in insectivores and frugivores richness in riparian forests most affected by these changes. Consequently, our study suggests communities do not tolerate reduction in riparian forest width or disturbance intensification without negative impact on FD, and this becomes more critical for riparian area <400‐m wide or with more than 60% disturbance. This minimum riparian width required to maintain FRed is greater than the minimum width required for riparian forests by Brazilian law. Thus, it is important to consider mechanisms to expand riparian habitats and reduce the disturbance intensity in riparian forests so that riparian bird community FD may be effectively conserved. Abstract : Here, we assess the impact of habitat loss and disturbance on Functional Diversity (FD) components Functional Redundancy (FRed), Functional Evenness (FEve), and Functional Richness (FRic) of riparian forest bird assemblages to evaluate (a) how FD components respond to riparian forest width reduction and vegetation disturbance; (b) the existence of thresholds within these relationships; (c) which of the main birds diet guild (frugivores, insectivores, and omnivores) respond to such thresholds. We predict that FD components will be affected negatively and nonlinearly by riparian changes.